Pengaruh Tax Amnesty, Sosialisasi Pajak, dan Kepatuhan Wajib Pajak Terhadap Penerimaan Pajak - Azizah, Tyara Nur; Hertati, Lesi; Pebriani, Reny Aziatul (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
This study aims to analyze the influence of tax amnesty, tax socialization, and taxpayer compliance with tax revenue. The object of the study is corporate taxpayers registered at KPP Pratama Ilir Barat, Palembang City. The determination of the sample using the Slovin formula with an error rate of 5% resulted in 100 corporate taxpayers as respondents. The research uses a quantitative approach with data collection through questionnaires distributed using google forms. Data analysis used SPSS 30 with multiple linear regression test. The results of the F test showed that tax amnesty, tax socialization, and taxpayer compliance simultaneously had a significant effect on tax revenue with a significance value of 0.001 < 0.05. Partially, the tax amnesty variable had a significant effect with a value of sig. 0.041 < 0.05 and a t-count value of 2.071 > t-table 1.985, tax socialization had a significant effect with a value of sig. 0.002 < 0.05 and t-count 3.231 > t-table 1.985, and taxpayer compliance had a significant effect with The value of sig. 0.009 < 0.05 and t-count 2.683 > t-table 1.985. This research provides practical implications in the form of recommendations to increase the effectiveness of tax socialization and strategies to increase taxpayer compliance to optimize tax revenue, as well as the need to develop a tax amnesty program with a more attractive scheme to encourage the disclosure of unreported assets.